An Excellent Electrochemical Sensor Based on Highly Porous Gold Film Modified Gold Electrode for Detecting Quercetin in Food and Medicine. Issue 4 (17th February 2020) - Liu, Yanyan; Xie, Ruirui; Yang, Peipei; Lu, Ling; Shen, Lin; Tao, Jia; Liu, Zhi; Zhao, Peng
Abstract : Quercetin is one of the most important nutrients in human daily diet, the accurate and efficient analytical approaches for quercetin is highly required as it's closely related to many biological activities. In this paper, the three-dimensional highly porous gold film (hp-Au) modified gold electrode (Au) was prepared by a facile two steps self-templating method, it was found that hp-Au possess high surface-to-volume ratio and excellent conductivity. Combining with the multiple merits of hp-Au, the hp-Au/Au showed an excellent detection performance towards quercetin compared with bare electrode and Au nanoparticles modified gold electrode (AuNPs/Au), the detection limit was 3.9 nM in a wide concentration range from 20 nM to 100 μ M. Meantime hp-Au/Au also showed decent stability, satisfied selectivity and desirable reproducibility. Moreover, the practical application of this sensor was verified by detecting QR in drink or food and medicine samples and the satisfactory recoveries of 97.43% to 101.59% and low RSD value (n = 3) no more than 3% were obtained.